Enhancement of Raman scattering in dielectric nanostructures with electric and magnetic Mie resonances - Frizyuk, Kristina (2018)
Resonantly enhanced Raman scattering in dielectric nanostructures has been recently proven to be an efficient tool for nanothermometry and for the experimental determination of their mode composition. In this paper we develop a rigorous analytical theory based on the Green's function approach to calculate the Raman emission from crystalline high-index dielectric nanoparticles. As an example, we consider silicon nanoparticles which have a strong Raman response due to active optical phonon modes. We relate enhancement of Raman signal emission to the Purcell effect due to the excitation of Mie modes inside the nanoparticles. We also employ our numerical approach to calculate inelastic Raman emission in more sophisticated geometries, which do not allow a straightforward analytical form of the Green's function. The Raman response from a silicon nanodisk has been analyzed with the proposed method, and the contribution of various Mie modes has been revealed.